Insentif Perpajakan Selama Dua Dekade: Systematic Literature Review (Jurnal Kendali Akuntansi, 2024)
This study aims to provide empirical evidence on the development of tax incentives studies in Indonesia. This study analyzes thirty-nine articles on tax incentives from twenty-five nationally accredited journals Sinta 1 and Sinta 2 during the 2003-2023 period. Articles were analyzed using the charting fields approach and analysis in qualitative studies to provide a broad explanation regarding the development of tax incentive studies. This study found that the implementation of various tax incentive policies still encounters various obstacles such as inconsistent regulations, standardization of tax officials' understanding, lack of outreach, and policies that are less relevant and not yet very beneficial. This study also found inconsistencies in previous research, so further studies are needed. The structureon, there is a phenomenon that the structure of company ownership and corporate governance is an indication of taxpayer non-compliance. Efforts to avoid taxes and efforts to prosper investors that have the potential to cause litigation risk.